Navigating Tariffs through Trade Diplomacy: Strategies and Lessons from Select Countries - Dionisio, Gary Ador; Katigbak, Jovito Jose (Theoretical and Practical Research in Economic Fields; Vol 16 No 4 (2025): TPREF Special Issue, Volume XVI, Issue 4(36), Winter 2025, 2025)
This paper explores the vital role of trade diplomacy in navigating the global economic volatility spurred by the broad-based US tariffs imposed since January 2025, which were anchored on national security concerns. More specifically, it reviews the trade diplomacy tactics employed by Canada, Germany, Mexico, and Vietnam vis-à-vis the US tariffs. Using a qualitative, descriptive methodology, the findings reveal both similarities and differences in their approaches. On one hand, all countries deployed a multi-pronged strategy and are pursuing trade diversification efforts to de-risk from great powers such as the US and China. Further, initiatives are being intensified to promote domestic industry resilience while balancing political, economic, social, and geostrategic factors. On the other hand, advanced economies (Canada and Germany) adopted a "retaliate-to-negotiate" approach, matching US tariffs tit-for-tat and filing WTO complaints while emerging economies (Mexico, Vietnam) used a "concession-to-de-escalate" strategy, delaying retaliation and offering proactive concessions on security, non-tariff barriers, and major purchases to secure lower tariff rates. The study also finds that countries with existing FTAs (Canada, Mexico) were significantly shielded from the tariffs. This paper thus provides a timely analysis of key trade diplomacy strategies amid unilateral, reciprocal tariffs and outlines practical lessons for other economies operating in a fragmented and increasingly protectionist economic landscape.